ANALYSIS OF INVENTORY COST EFFICIENCY ON LEVERAGE ITEMS: A CASE STUDY ON A MACHINERY AND EQUIPMENT MANUFACTURER - Sulungbudi, Brigita Meylianti; Jingga, Tomi Dwi (Jurnal Mebis, 2023)
This study aims to determine inventory management for an agricultural machinery and equipment manufacturer. The manufacturer has not yet implemented any inventory management, therefore, it often experiences overstock and understock. The study employed Kraljic’s matrix as a classification method and employed a complete aggregation method to find the optimal ordering frequency for leverage raw materials. Due to the fluctuation of demand and supply, the numbers of safety stock and the reorder point were calculated in addition to the ordering frequency and ordering quantities. The inventory model was developed using secondary inventory data analysis of 2019. Data were collected before the pandemic because it was expected that these data would be similar to the current situation. By implementing this method, PD KMU is expected to reduce its inventory costs by IDR6,940,310,00 than those in the past.